Analysis of proton bunch parameters in the AWAKE experiment. (24th November 2021) - Hafych, V.; Caldwell, A.; Agnello, R.; Ahdida, C.C.; Aladi, M.; Amoedo Goncalves, M.C.; Andrebe, Y.; Apsimon, O.; Apsimon, R.; Bachmann, A.-M.; Baistrukov, M.A.; Batsch, F.; et al.
Abstract: A precise characterization of the incoming proton bunch parameters is required to accurately simulate the self-modulation process in the Advanced Wakefield Experiment (AWAKE). This paper presents an analysis of the parameters of the incoming proton bunches used in the later stages of the AWAKE Run 1 data-taking period. The transverse structure of the bunch is observed at multiple positions along the beamline using scintillating or optical transition radiation screens. The parameters of a model that describes the bunch transverse dimensions and divergence are fitted to represent the observed data using Bayesian inference. The analysis is tested on simulated data and then applied to the experimental data.